Enhancing Financial Literacy in Higher Education: Modeling Student Perceptions of Cryptocurrency Through Trust, Risk, and Confidentiality Factors - Kumari, Pooja; Srivastava, Alpana; Rastogi, Rupesh (International Review of Management and Marketing, 2026)
This study investigates how trust, perceived risk and confidentiality shape university students’ attitudes toward cryptocurrency within the broader goal of enhancing financial literacy in higher education. As digital financial tools become more prevalent, understanding how learners interpret these determinants is essential for designing curricula that prepare them for emerging financial environments. The study models the combined influence of these psychological constructs to inform financial literacy policy and educational practice. A quantitative research design was applied using a secondary dataset of 891 university students. Constructs related to perceived security, confidentiality, risk and attitudes toward cryptocurrency were operationalised through validated multi-item Likert scales. A variance-based structural modelling approach was used to assess reliability, validity and structural relationships among latent constructs. Regression coefficients were estimated using standardised composite measures, and predictive accuracy was evaluated through bootstrap testing and ten-fold cross-validated Q2 statistics. Security and confidentiality perceptions showed a strong positive influence on student attitudes toward cryptocurrency, while perceived risk demonstrated a smaller yet significant positive effect. The structural model accounted for a meaningful proportion of attitudinal variance and exhibited moderate predictive relevance. These findings indicate that students rely heavily on perceived system trustworthiness, and that risk sensitivity does not necessarily diminish favourable attitudes, suggesting a nuanced interpretation of cryptocurrency within this population. This study contributes to the limited empirical research focusing specifically on cryptocurrency perceptions among university students. By integrating psychological determinants with financial literacy considerations, it provides a model that captures how learners evaluate emerging financial technologies. The findings offer evidence-based insights that support the development of digital financial literacy initiatives and inform higher education policy on preparing students for participation in digital financial ecosystems.